SISTEM PAKAR DIAGNOSA KERUSAKAN PADA AUTOMATIC TELLER MACHINE BERBASIS WEB (Information Technology and Telematics, 2013)
Automatic Teller Machine (ATM) is one of a set of banking products in the form of an electronic device which is provided to serve the banking transactions are very popular in the community at this time. One of the electronic delivery channel has become the spearhead or a flagship company engaged in financial services, especially in banking. With increasing transaction at an ATM, the ATM machine performance in serving the customer must be able to work as optimally as possible by pressing the least possible damage. Damage to the ATM machine was not operating result / can not be used for transactions by customers. Of these conditions to be aware of the problems and maximize the performance of the system at the ATM machine, it is necessary to know the working principle of the ATM machine and pheriperal anything associated with the machine. To know what the problem is happening in damage to the Automatic Teller Machine (ATM) which is then implemented into the Expert System, the next problem encountered was the amount of experts in this area is limited so take the time to incorporate the ability of experts to produce conclusions about the criteria, characteristics , specifications and other types of damage to the ATM. Keywords : expert system,ATM